Structure and parasitism of egg-batches of a processionary moth population different from Thaumetopoea pityocampa (Den. & Schiff.) (Lep. Thaumetopoeidae) found in Bulgaria (Bollettino di zoologia agraria e bachicoltura, 2024)
A population of apine processionary moth was studied near Banya in Bulgaria, which differs from Thaumetopoea pityocampa (Den. & Schiff.) in its biology. The caterpillars reach the 5th larval instar already in October and hibernate in the soil as prepupae until March. Two generations were studied found on Pinus nigra Arnold. In all cases, oviposition occurred from the base to the tip of the needle. The mean number of eggs per batch was found to be 237 and 247. The oviposition period was estimated to range from midth of June to midth of July and the host embryonic development required some 29 days. The hatching rate ofthe host was found to be 76.9 and 69.2%, where the impact of egg parasitoids accounted 15.8% and 24.5%, respectively. Ooencyrtus pityocampae (Mercet) was the most abundant egg parasitoid. Additionally, Baryscapus servadeii (Dom.), Anastatus bifasciatus (Fonsc.), Trichogramma embryophagum (Htg.) and Macroneura vesicularis (Retzius) were recorded. Most of the egg parasitoids emerged during the embryonic development of the host. For O. pityocampae a developing period of 2-3 weeks was calculated. About 26% of all emerged O. pityocampae appeared during the consecutive year, mainly in April-May. Only T. embryophagum preferred the eggs on the basal part of the batch for parasitism. Tettigoniids were observed as predators.
Keywords: Thaumetopoea sp.; egg parasitoids; Ooencyrtus pityocampae; parasitism rate; Trichogramma embryophagum; Bulgaria